2018
DOI: 10.1002/app.47129
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of magnesium hydroxide and its application in flame‐retardant oil‐extended styrene–ethylene–butadiene–styrene/polypropylene composites

Abstract: Magnesium hydroxide (MH) was modified with triethoxysilane and polymethyl-vinyl silicone rubber and used to prepare flame-retardant oil-extended styrene-ethylene-butadiene-styrene (O-SEBS)-polypropylene (PP) composites. The water contact angle of modified magnesium hydroxide (MMH) reached 141 ; this indicated that MMH possessed excellent hydrophobic properties. The samples (1.6 mm) passed the UL-94 V-0 rating during vertical burning tests when the loading amount of MH or MMH was 70 wt %. This indicated the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Consequently, in order to improve the flame‐retardance and mechanical properties of materials, the functional inorganic particles have attracted wide attention . Liu et al . used triethoxysilane and polymethyl–vinyl silicone rubber to modify MH and to prepare flame‐retardant polypropylene composites, the results showed that the compatibility between inorganic particles and matrix obviously increased, and the modification did not decrease the flame‐retardant properties of MH.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in order to improve the flame‐retardance and mechanical properties of materials, the functional inorganic particles have attracted wide attention . Liu et al . used triethoxysilane and polymethyl–vinyl silicone rubber to modify MH and to prepare flame‐retardant polypropylene composites, the results showed that the compatibility between inorganic particles and matrix obviously increased, and the modification did not decrease the flame‐retardant properties of MH.…”
Section: Introductionmentioning
confidence: 99%
“…It was evident that the total evolved pyrolysis products were diminished with the addition of PPAP during pyrolysis process, as shown in Figure 10A,B. The representative pyrolysis products of pure UPR thermosets were water (3665 cm −1 ), hydrocarbons (3070, 3038, 2975, and 2877 cm −1 ), CO 2 (2371 and 2327 cm −1 ), CO (2180 cm −1 ), carbonyl compounds (1764 cm −1 ), aromatic compounds (1605, 1599, and 1502 cm −1 ), and aliphatic polyester (1251, 1177, and 1035 cm −1 ) . With the incorporation of PPAP, the characteristic peaks of UPR/PPAP thermosets were nearly similar with those of pure UPR, but the new peak corresponded to ammonia appeared at 930 cm −1 and the peak intensity of water was evidently increased, which indicated that the more nonflammable gases generated from UPR/PPAP thermosets exerted the dilution effect in gas phase compared with pure UPR.…”
Section: Resultsmentioning
confidence: 95%
“…16 This compatibility problem caused by agglomeration affects the ame retardant efficiency of MH as a ame retardant and destroys the mechanical properties and processability of the matrix material to a large extent. [18][19][20] Simple physical blending between an inorganic ller and the polymer matrix is unsatisfactory, especially in the case of high ller loading. 20,21 Han et al 22 introduced MH nanoparticles into cellulose aerogels through the blending method.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, good dispersibility and stable interfacial adhesion strength between MH and the polymer matrix are needed for MH to execute an excellent ller function. 23 To solve this problem effectively, most researchers have focused on the modication of MH by using silane coupling agents, 18,24,25 saturated or unsaturated high fatty acid salts, 23,26,27 titanate coupling agents 28,29 and other modiers. 24,29 The introduction of these modiers improves the dispersion of MH to varying degrees, but it is accompanied with new process costs and environmental problems.…”
Section: Introductionmentioning
confidence: 99%